THE NEEDS OF COMPETENCY ASSESSMENT IN STEM EDUCATION: A SYSTEMATIC LITERATURE REVIEW - Ng Chee Hoe; Mazlini Adnan, (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
STEM (Science, Technology, Engineering, and Mathematics) education has become a major educational program in most developing countries to provide talented workforces for economic development. In developing future workforces, the need for competency assessments in STEM education has become a major concern, and the way of implementing the assessment has also been discussed for over a decade. Competency assessment in STEM education is essential to ensuring students possess the knowledge, STEM skills, and attitudes in the STEM field. In this paper, a systematic literature review used the PRISMA framework to evaluate the need for competency assessment, synthesize current research on assessment in STEM education, and identify the prevalent assessment methods, challenges, and best practices. Following the PRISMA guidelines, a review across Scopus, Emerald, Science Direct, and Springer Link databases was screened based on the predefined inclusion and exclusion criteria. The findings found that most indicated mono-disciplined standardized assessments, project-based assessments, 21st-century skills, and interest in the mono-disciplinary. This finding highlights the urgent need for a competency assessment model in STEM education by improving the effectiveness of competency assessment to enhance STEM education outcomes.